Automated Sales Processes for the Automotive Sales Industry - Merla, Patrik (My University, 2023)
This thesis describes the iterative improvement of an automated sales process in an automotive sales company. The company is looking to improve its current automated sales efforts to reach more customers with better resource efficiency to find an edge over the competitive market. The thesis uses design science research, where an artifact is created or improved to solve a business problem presented by the case company. The case company wanted to enable sales staff to be in touch with their existing customers on an increased rate. To solve this issue, an improved automated sales process was created to enable higher outreach by the sales staff. The new improved automated sales process took into consideration new kinds of customer data and customer retention -related measures, that were discovered from literature. The creation process follows existing literature, utilizing existing knowledge, and creating newfound knowledge from the iterative design process. The existing automated sales process worked as a starting point for the improved artifact, taking in improvements from both literature and expert interviews. As proposed by the literature, formal interviews were conducted to establish the information needs of the improved artifact. The final product is a new automated sales process that can be implemented to improve the case company's operations. The thesis' objective is to provide insight into automated sales processes in the automotive sales industry, as well as to support previous theoretical results on automated sales processes, customer retention, and the use of design science to solve business problems. Furthermore, as is the goal of design science research, the structural business problem in the case company was solved to a considerable extent.

Tämä opinnäytetyö kuvaa automatisoidun myyntiprosessin iteratiivista parantamista autokaupassa. Toimeksiantaja pyrkii parantamaan nykyistä automatisoitua myyntiprosessiaan tavoittaakseen enemmän asiakkaita paremmalla resurssitehokkuudella saavuttaakseen etulyöntiaseman kilpailluilla markkinoilla. Opinnäytetyössä käytetään metodologiana suunnittelutiedettä, jossa luodaan tai parannetaan artefakti toimeksiantajan esittämän liiketoimintaongelman ratkaisemiseksi. Toimeksiantaja halusi antaa myyntihenkilöstölle mahdollisuuden olla yhteydessä olemassa oleviin asiakkaisiinsa entistä resurssitehokkaammin. Tämän ongelman ratkaisemiseksi luotiin paranneltu automatisoitu myyntiprosessi, joka mahdollistaa myyntihenkilöstön tehokkaamman asiakaskontaktoinnin. Uusi automatisoitu myyntiprosessi otti huomioon kirjallisuudessa esitetyt laajemmat asiakastietojen attribuutit ja asiakaspitoon liittyvät toimenpiteet. Kehitysprosessissa hyödynnetään olemassa olevaa kirjallisuutta, sekä yrityksen käytettävissä olevaa tietoa ja luodaan sitä kautta uutta tietoa iteratiivisesta suunnitteluprosessista. Parannellun artefaktin lähtökohtana toimi olemassa oleva automatisoitu myyntiprosessi, jolle tunnistettiin kehityskohtia sekä kirjallisuudesta että asiantuntijahaastatteluista. Kirjallisuuden ehdotusten mukaisesti suoritettiin muodollisia haastatteluja parannetun prosessin tietotarpeiden selvittämiseksi. Lopputuloksena on uusi automatisoitu myyntiprosessi, jonka avulla voidaan paremmin ratkaista toimeksiantajan liiketoimintaongelma. Opinnäytetyön tavoitteena on antaa näkemys automyynnin automatisoiduista myyntiprosesseista sekä tukea aikaisempia teoreettisia tuloksia automatisoiduista myyntiprosesseista, asiakaspidosta ja suunnittelutieteen käytöstä liiketoiminnan ongelmien ratkaisemisessa. Lisäksi suunnittelutieteen tutkimuksen tavoitteen mukaisesti toimeksiantajan liiketoimintaongelma ratkesi suurelta osin.
Keywords: Automotive Sales Industry, Business Process Automation, Automotive Sales Process, Customer Data, Sales Automation, Design Science Research, Robotic Process Automation